Antioxidant Effect Of Citrullus Colocynthis On Alloxan Induced Diabetic Rats - K.A, Jeyanthi (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Aqueous extract of Citrullus colocynthis was screened for its antioxidant effect in alloxan induced diabetic rats. Preliminary phytochemical screening of the plant shows the presence of large amount of terpenoids, phenolics and flavanoids. The presence of phenolic compound prompted us to evaluate its antioxidant effect. An appreciable decrease in peroxidation products was observed in C. colocynthis (300 mg/kg body wt.) treated diabetic rats. The decreased activities of key antioxidant enzymes such as SOD, CAT, GSH and Gpx in diabetic rats were brought back to near normal range upon C. colocynths treatment.